KREATIVITAS GURU DITINJAU DARI KEPEMIMPINAN TRANFORMASIONAL KEPALA SEKOLAH DAN KOMUNIKASI INTERPERSONAL - Hasbu Burhanudin; Rita Retnowati; Griet Helena Laihad (JURNAL MANAJEMEN PENDIDIKAN, 2022)
REVIEWING TEACHER CREATIVITY USING PRINCIPAL TRANSFORMATIONAL  LEADERSHIP AND INTERPERSONAL COMMUNICATIONThis research was conducted to study the relationship between principal transformational leadership and interpersonal communication altogether with teacher creativity. The study was conducted at 10 Private Junior High Schools in Cibadak Subdistrict, Sukabumi Regency, West Java Province in 2020. The population of this study were 201persons and 134  samples were selected using Proportional Random Sampling technique. The method used was conducting a survey and data analysis techniques utiliing statistical correlation and simple linear regression and multiple linear regression. The study came up with three results as follows; firstly, there was a significant positive relationship between the principal transformational leadership (X1) and teacher creativity (Y) where the regression coefficient Ŷ=71,347 +0.4328X1, the correlation coefficient ry1 = 0.6519 and the coefficient of determination r2y1 was 0.4250. Secondly, there was a significant positive relationship between Interpersonal Communication variable (X2) and Teacher Creativity (Y) which expressed in the form of a regression equation Ŷ = 49.074 + 0.6117 X2 and correlatioin coefficient ry2 = 0.7493 and also determination coefficient r2y2 = 0.5614. Thirdly, there was a significant positive relationship between the principal transformational leadership variable (X1) and interpersonal communication (X2) altogether to teacher creativity (Y) which expressed in the form of a regression equation Ŷ = 19.194 + 0.238 X1 +0.604 X₂ and the correlation coefficient Ry12 was 0.7754 and also the coefficient of determination R_y12 ^ 2 was 0.6013. Based on these findings it could be concluded that teacher creativity c be improved through the principal's transformational leadership and interpersonal communication.